TGF-β Affects the Differentiation of Human GM-CSF+ CD4+ T Cells in an Activation- and Sodium-Dependent Manner - Éliás, Szabolcs; Schmidt, Angelika; Kannan, Venkateshan; Andersson, John; Tegnér, Jesper (Frontiers in Immunology, 2016)
The cytokine GM-CSF is involved in the pathogenesis of chronic inflammatory diseases such as Multiple Sclerosis. However, the environmental cues promoting differentiation of GM-CSF producing T cells are unclear. Herein, we performed a broad experimental screening of cytokines and data-driven analysis assessing their ability to induce human GM-CSF+ CD4+ T cells and their subpopulations. TGF-b was discovered to induce GM-CSF production independently of proliferation and IL-2 signaling including STAT5. In contrast, IL-6 and IL-23 decreased GM-CSF production. On the population level, GM-CSF induction was highly correlated with expression of FOXP3 across cytokine stimulations but not with that of IL-17. However, on single cell level GM-CSF and IFN-g expression were most correlated, independently of the cytokine environment. Importantly, under low sodium conditions in the medium or upon stimulation with plate-bound instead of bead-bound anti-CD3 and anti-CD28 antibodies, the effects of TGF-b on GM-CSF, but not on FOXP3, were reversed. Our analysis indicates a novel role for TGF-b in generating GM-CSF+ subsets of human CD4+ T cells. These results are important for understanding of autoimmune disease and therapeutic considerations.